2013
DOI: 10.1016/j.ejvs.2013.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Compression Stockings after Endovenous Laser Ablation of the Great Saphenous Vein: A Prospective Randomized Controlled Trial

Abstract: Prescribing compression stockings for longer than 2 days after endovenous GSV ablation (without simultaneous phlebectomies) leads to reduced pain and improved physical function during the first week after treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0
4

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 14 publications
3
54
0
4
Order By: Relevance
“…[21][22][23][24] One randomised controlled trial did link compression to reductions in pain, bruising and phlebitis after thermoablation, 25 but others have failed to make any links. 9,10,26 Historically, compression was used for at least two to three weeks after sclerotherapy. 27 A previous survey of members of the VSGBI by Edwards et al 28 in 2006 reported that 99% of respondents routinely used compression after varicose vein interventions but there was significant variation in the duration of compression with a range of 6 h to three months (however, this survey included patients treated by open surgery and other methods).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[21][22][23][24] One randomised controlled trial did link compression to reductions in pain, bruising and phlebitis after thermoablation, 25 but others have failed to make any links. 9,10,26 Historically, compression was used for at least two to three weeks after sclerotherapy. 27 A previous survey of members of the VSGBI by Edwards et al 28 in 2006 reported that 99% of respondents routinely used compression after varicose vein interventions but there was significant variation in the duration of compression with a range of 6 h to three months (however, this survey included patients treated by open surgery and other methods).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, evidence has emerged which suggests that a shorter duration (or even no compression) after UGFS may be associated with similar outcomes to more prolonged regimes and there seems to have been a reduction in the duration commonly used. [9][10][11][29][30][31] The NICE Clinical Guideline recommends compression for no longer than seven days, but with the clear qualification that there is insufficient evidence in the literature on which to base a clear recommendation on the degree of compression, the method or the duration. 32 If compression of a certain type and/or duration were shown to be associated with improved vein ablation rates after UGFS or endothermal treatment then this would clearly be important information, because truncal vein ablation is considered to be the mainstay of a good long-term result and of minimising the need for further treatments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bu bilgilendirme hemşireler tarafından yapılması gerekmektedir. [10,14,15,33] [34] Hemşireler hastalarına AEÇ ile ilgili şu başlıklar altında bilgilendirme yapması gerekmektedir. [15,35] • Antiembolik çorap giymek neden gereklidir?…”
Section: Antiembolik çOrap Bakım Protokolüunclassified
“…• En son hastaya çorabın konforlu olup olmadığı sorulmalıdır. [10,33] Bakker ve diğerlerinin (2013) yaptıkları çalışmada hastaların AEÇ'ların uzun süre kullanımından rahatsız oldukları yönünde gözlem yaptıkları bildirilmiştir. [33] Antiembolik çorabın bakımı ve değerlendirilmesi ile ilgili adımlar; (Şekil 6)…”
Section: Antiembolik çOrap Giydirilmesi Ile Ilgili Adımlar; (şEkil 3)unclassified